The acquisition of phonological alternations: The case of the Mandarin tone sandhi process. (November 2019) - Tang, Ping; Yuen, Ivan; Rattanasone, Nan Xu; Gao, Liqun; Demuth, Katherine
Abstract: Phonological processes can pose a learning challenge for children, where the surface form for an underlying contrast may vary as a function of the phonological environment. Mandarin tone sandhi is a complex phonological process that requires knowledge about both the tonal and the prosodic context in which it applies. The present study explored the productive knowledge of tone sandhi processes by 108 3- to 5-year-old Mandarin-speaking children and 33 adults. Participants were asked to produce novel tone sandhi compounds in different tonal contexts and prosodic structures. Acoustic analysis showed that 3-year-olds have abstracted the tone sandhi process and can productively apply it to novel disyllabic words across tonal contexts. However, even 5-year-olds still differed from adults in applying tone sandhi in response to the trisyllabic prosodic structure. The results are discussed in terms of the factors that influence how tone sandhi processes, and phonological alternations more generally, are acquired.